Phonetics Applied to English for Specific Purposes in 5th year-medicine Students. - Elizabeth Mercedes Monagas Alvarez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2008)
Background: Pronunciation of the English language has always been one of the biggest problems in our Spanish speaker students not only at different levels but also at different kinds of teaching. It is still a troublesome area where the majority of the students continue without establishing a correct communication with English speaker people. Objective: to elaborate a methodological strategy that allows the development of pronunciation skills in English with medical purpose in 5th year students. Methods: a quantitative qualitative comparative study developed in three groups of medicine students in the 5th academic year. A methodological strategy was developed to teach pronunciation. Mid term test and well as the final test were the most important variables to carry out this investigation. Surveys and class observation method were also applied. Results: The per cent of students evaluated as excellent and good in the final test (5 and 4) was elevated in regard to the mid term test in the first semester. None of them failed the oral final and written test. Conclusions: The methodological strategy elaborated for the 5th year students of the medicine specialty highly contributed to solve great part of the pronunciation problems developing pronunciation skills.